Evaluasi tingkat pengetahuan pasien terhadap penggunaan obat diabetes mellitus tipe II dirawat jalan rumah sakit Advent Medan - Windi Darantika; Rena Meutia (Journal of Pharmaceutical and Sciences, 2023)
The importance of one's health cannot be overstated, especially in today's world where many individuals suffer from numerous illnesses, including diabetes mellitus. Is there a correlation between patients' degree of awareness regarding the use of type II Diabetes Mellitus medications at Medan Adventist Hospital? is how the problem from this study is formulated. The goal of the study was to ascertain how patients' level of familiarity with the usage of type II Diabetes Mellitus medications at Medan Adventist Hospital correlated with their condition. This study is cross-sectional and analytical descriptive in nature. Patients with type II Diabetes Mellitus in the outpatient facility of Medan Adventist Hospital were surveyed prospectively in order to collect data. Data from patient medical records is also used in data collection. The study's findings include the knowledge of patients based on their age, gender, education level, occupation, length of suffering, medical history, and knowledge level. The findings are based on the knowledge levels of 100 respondents, of whom 42 (42%), 50 (50%), and 8 (8%), respectively, had good levels of knowledge, good levels of knowledge that were sufficient, and inadequate levels of knowledge. According to the findings of a study done at Medan Adventist Hospital, type II Diabetes Mellitus patients there had an average level of knowledge about drug use, with 50 respondents (or 50%) falling into this category.